Evidence-Based Performance Measures for Rhinoplasty: A Multidisciplinary Performance Measure Set. Issue 2 (24th November 2020) - Manahan, Michele A.; Fedok, Fred; Davidson, Caryn; Ahmad, Jamil; Constantinides, Minas; Davis, Richard; Friedman, Oren; Gilman, Robert; Ishii, Lisa; Keyes, Geoffrey; Lin, Samuel J.; Marcus, Benjamin; et al.
Abstract : Summary: The American Society of Plastic Surgeons, the American Academy of Otolaryngology–Head and Neck Surgery, and the American Academy of Facial Plastic and Reconstructive Surgery commissioned the multidisciplinary Rhinoplasty Performance Measure Development Work Group to identify and draft quality measures for the care of patients undergoing both functional and aesthetic rhinoplasty. One outcome measure and three process measures were identified. The outcome looked at patient satisfaction with rhinoplasty procedures. The process measures look at motivations and expectations of the procedure, airway assessment, and nonnarcotic shared decision-making strategies for pain management. All measures in this report were approved by the American Society of Plastic Surgeons Quality and Performance Measures Work Group and Executive Committee, and the American Academy of Otolaryngology–Head and Neck Surgery Foundation, the American Academy of Facial Plastic and Reconstructive Surgery, The Rhinoplasty Society, and the American Association of Oral and Maxillofacial Surgeons. The Work Group recommends the use of these measures for quality initiatives, Continuing Medical Education, Maintenance of Certification, Qualified Clinical Data Registry reporting, and national quality reporting programs.